Learning to suppress a location is configuration-dependent - Gao, Ya (2023)
Where and what we attend is very much determined by what we have encountered in the past. Recent studies have shown that people learn to extract statistical regularities in the environment resulting in attentional suppression of locations that were likely to contain a distractor, efectively reducing the amount of attentional capture. Here, we asked whether this suppression efect due to statistical learning is dependent on the specifc confguration within which it was learned. The current study employed the additional singleton paradigm using search arrays that had a confguration consisting of set sizes of either four or 10 items. Each confguration contained its own high probability distractor location. If learning would generalize across set size confgurations, both high probability locations would be suppressed equally, regardless of set size. However, if learning to suppress is dependent on the confguration within which it was learned, one would expect only suppression of the high probability location that matched the confguration within which it was learned. The results show the latter, suggesting that implicitly learned suppression is confguration-dependent. Thus, we conclude that the high probability location is learned within the confguration context within which it is presented